Arthroscopic Rotator Cuff Surgery A Practical Approach to Management - Abrams, Jeffrey S.; Abrams, Jeffrey S.; Bell, Robert H.; Bell, Robert H. (Springer New York : Imprint: Springer, 2008)
This cutting-edge text is written by pioneers in the field who guide the reader through the technical steps of rotator cuff procedures. In keeping with growing patient demand for less invasive treatments, emphasis is placed on arthroscopy. The timely book answers key questions raised at instructional courses, such as how to convert from mini-open repair to all arthroscopic repair. The fundamentals, including patient positioning, suture anchor options, and knot tying, are covered in addition to state-of-the-art techniques. Clavicle resection, tendon to tuberosity repair, PASTA repair, large and massive repair techniques, and subscapularis repairs are among the approaches detailed. The book also presents margin convergence repair, interval slides, matrix grafts, and biceps tendon disorders. Chapters on mechanics and healing, postoperative rehabilitation, and avoiding complications complete the book. The step-by-step approach of the text is supplemented by a wealth of illustrations and photographs. Orthopedic residents and experienced surgeons will find the clinical pearls highlighted throughout the book.